Ferroptosis Driver SOCS1 and Suppressor FTH1 Independently Correlate With M1 and M2 Macrophage Infiltration in Head and Neck Squamous Cell Carcinoma - Hu, Zhang-Wei; Wen, Yi-Hui; Ma, Ren-Qiang; Chen, Lin; Zeng, Xue-Lan; Wen, Wei-Ping; Sun, Wei (Frontiers in Cell and Developmental Biology, 2021)
Objective: To investigate the role of ferroptosis, an iron-dependent form of nonapoptotic cell death, in the HNSCC immune microenvironment. Materials and Methods: A list of ferroptosis-related genes was obtained from the FerrDb database. Gene expression data were acquired from The Cancer Genome Atlas (TCGA) and analyzed using the R language. Protein–protein interaction analysis was conducted using STRING and GeneMANIA. The correlations between gene expression levels and a patient’s survival were analyzed using GEPIA, the Kaplan–Meier estimate, and a multivariate Cox proportional hazards model. The expression results were verified using Oncomine and Human Protein Atlas data. We used the TIMER, GEPIA2, GEPIA2021 and TIMER2 databases to investigate the relationships between gene expression and infiltrating immune cells. Results: Analysis of differentially expressed genes (DEGs) identified 9 each ferroptosis drivers and ferroptosis suppressors, among which four genes correlated with survival as follows: two drivers (SOCS1, CDKN2A) associated with better survival and two suppressors (FTH1, CAV1) associated with poorer survival. Multivariate Cox survival analysis identified SOCS1 and FTH1 as independent prognostic factors for HNSCC, and their higher expression levels were verified using Oncomine and HPA data. The results acquired using TIMER, GEPIA2, GEPIA2021 and TIMER2 data revealed that the driver SOCS1 and the suppressor FTH1 independently correlated with M1 and M2 macrophage infiltration. Conclusions: The ferroptosis driver SOCS1 and suppressor FTH1 are independent prognostic factors and that correlate with M1 and M2 macrophage infiltration in HNSCC. Targeting ferroptosis-immunomodulation may serve as a strategy to enhance the activity of immunotherapy.